2016
DOI: 10.5352/jls.2016.26.3.289
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Antithrombosis Activity of Different Parts of Sorbus commixta from Ulleung Island

Abstract: Sorbus commixta, a flowering plant in the Rosaceae family, is native to Japan and Ulleung Island, Korea. This plant is also called maga-mok or mai-mok in Korea because the bud of the stem has a similar shape to the teeth of a horse. In this study, hot water extracts from different parts of S. commixta, such as leaf, stem, and immature and mature fruits, were prepared, and their antithrombosis and antioxidant activities were evaluated. The extraction yield and pH of stem extracts were 3.99% and 5.5, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The anticancer activity of the bars of S. commixta has been previously reported, [7] but whether single compounds have the anti-proliferation activity against cancer cells have not reported yet. Previous research on the plant had reported the isolation of sorbic acid, chalcone glucoside, prunasin, amygdalin and triterpenoids such as lupenone and lupeol [4,[8][9]. Recently, the methanol extract from the barks of S. commixta was shown to have antioxidant, anti-inflammatory and the potent radical scavenging activity [4,5].…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer activity of the bars of S. commixta has been previously reported, [7] but whether single compounds have the anti-proliferation activity against cancer cells have not reported yet. Previous research on the plant had reported the isolation of sorbic acid, chalcone glucoside, prunasin, amygdalin and triterpenoids such as lupenone and lupeol [4,[8][9]. Recently, the methanol extract from the barks of S. commixta was shown to have antioxidant, anti-inflammatory and the potent radical scavenging activity [4,5].…”
Section: Previous Studiesmentioning
confidence: 99%
“…It has used for the treatment of neuralgia, cough and expectorant in folk remedies [1][2][3]. Until now, the study on the S. commixta has been mainly focused on the berries of S. commixta, and their biological activities, antiinflammatory and antioxidant effect, have been studied [4][5][6]. The anticancer activity of the bars of S. commixta has been previously reported, [7] but whether single compounds have the anti-proliferation activity against cancer cells have not reported yet.…”
Section: Previous Studiesmentioning
confidence: 99%